Odontanthias grahami Randall & Heemstra, a junior synonym of Anthias xanthomaculatus Fourmanoir & Rivaton (Teleostei: Serranidae: Anthiadinae) - Gill, Anthony C.; Tang, Chi-Ngai (Zootaxa, 2022)
Although previously classified in the genus Pseudanthias Bleeker, 1871, the holotype of Anthias xanthomaculatus Fourmanoir & Rivaton, 1979 from New Caledonia was recently shown to be a juvenile specimen of the genus Odontanthias Bleeker, 1873, and possibly conspecific with Odontanthias grahami Randall & Heemstra, 2006 from eastern Australia. Meaningful comparison with the latter species was problematic as it was known only from four adult specimens. Recent collection of a size series of six specimens from the Lord Howe Rise confirms that the two nominal species are conspecific. Odontanthias grahami is therefore placed in the synonymy of A. xanthomaculatus.